2001
DOI: 10.1002/1522-2683(200101)22:2<334::aid-elps334>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Towards dynamic coating of glass microchip chambers for amplifying DNAvia the polymerase chain reaction

Abstract: As microchip technology evolves to allow for the integration of more complex processes, particularly the polymerase chain reaction (PCR), it will become necessary to define simple approaches for minimizing the effects of surfaces on the chemistry/processes to be performed. We have explored alternatives to silanization of the glass surface with the use of additives that either dynamically coat or adsorb to the glass surface. Polyethylene glycol, polyvinylpyrrolidone (PVP), and hydroxyethylcellulose (HEC) have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 26 publications
2
59
0
Order By: Relevance
“…On the other hand, passivation of the Si surface by silanization followed by a polymer coating showed good though inconsistent amplification, while SiO 2 performed best of all [214,215]. Alternatives to silanization for passivation of surfaces in glass PCR microchambers have also been explored by Giordano et al [216]. A distinctively different approach to on-chip PCR was introduced by Kopp et al [217].…”
Section: Clinical Dna By Microchip Pcrmentioning
confidence: 99%
“…On the other hand, passivation of the Si surface by silanization followed by a polymer coating showed good though inconsistent amplification, while SiO 2 performed best of all [214,215]. Alternatives to silanization for passivation of surfaces in glass PCR microchambers have also been explored by Giordano et al [216]. A distinctively different approach to on-chip PCR was introduced by Kopp et al [217].…”
Section: Clinical Dna By Microchip Pcrmentioning
confidence: 99%
“…favorable fluidic, optical and electrical insulating properties), high resistance to fluid and vapor diffusion during PCR, and hence used in most integrated PCR-CE devices (Hong et al 2001;Khandurina et al 2000;Lagally et al 2004;Prakash et al 2005;Rodriguez et al 2003;Waters et al 1998). The main drawback in using glass is its hydrophilicity which causes excessive adsorption of PCR reagents and requires careful tailoring and/or suitable modification of its surface properties (Erill et al 2003;Giordano et al 2001a;Obeid et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies for dynamic coating of glass microchip chambers for amplifying DNA via PCR have been investigated by the group of Landers [53]. While HEC was found to be suitable to deactivate microchannel surfaces to enable reliable DNA separations, it was observed that HEC at a concentration of 0.2% w/v significantly inhibited a-DNA amplification in polypropylene inserts.…”
Section: Coating Of Integrated Reactor Chambersmentioning
confidence: 99%